Manajemen Perioperatif pada Tindakan Eksisi Tumor Mammae dengan Anestesi Umum : Studi Kasus - Putri Dwi Minantry; Candrasari, Yuniani; Fransisco Putra Tjiku, Mario; Novitasari, Dwi; Budi S, Martyarini (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2026)
Mammary tumor is an abnormal growth in breast tissue that can be classified as either benign or malignant. Early detection and appropriate treatment are crucial to prevent complications and ensure optimal patient outcomes. This case study describes the perioperative management of a 44-year-old female patient diagnosed with left mammary tumor (tumor mammae sinistra), who underwent excision surgery. The research method applied was a descriptive observational design with a case study approach. Data were collected from medical records, physical examination, laboratory findings, imaging results, and continuous monitoring of vital signs during the preoperative, intraoperative, and postoperative periods. The findings showed that a comprehensive approach, including thorough preoperative assessment, careful anesthetic induction, precise surgical excision, and intensive postoperative monitoring, resulted in stable hemodynamic status and reduced the risk of perioperative complications. The patient demonstrated a favorable recovery with no recurrence observed in the short-term follow-up. In conclusion, comprehensive perioperative management in excision of a mammary tumor provides a positive prognosis and underscores the importance of multidisciplinary collaboration between surgical and anesthesia teams. Moreover, this case highlights the potential benefits of adopting similar protocols for patients undergoing mammary tumor surgery